2018
DOI: 10.1016/j.celrep.2018.01.087
|View full text |Cite
|
Sign up to set email alerts
|

A Roadmap for Human Liver Differentiation from Pluripotent Stem Cells

Abstract: Summary How are closely related lineages, including liver, pancreas, and intestines, diversified from a common endodermal origin? Here, we apply principles learned from developmental biology to rapidly reconstitute liver progenitors from human pluripotent stem cells (hPSCs). Mapping the formation of multiple endodermal lineages revealed how alternate endodermal fates (e.g., pancreas and intestines) are restricted during liver commitment. Human liver fate was encoded by combinations of inductive and repressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
180
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 86 publications
(162 reference statements)
5
180
0
2
Order By: Relevance
“…Is there only one "posterior foregut" route to generate pancreas, or are there multiple such routes, and if so, does the choice of intermediate route impact downstream pancreatic differentiation? Indeed, hPSC differentiation studies have suggested the existence of at least two types of posterior foregut, one poised for pancreatic, and the other primed for liver, differentiation in vitro (Ang et al, 2018). Third, while hPSC differentiation protocols endeavor to generate early Pdx1 + pancreatic progenitors, there is no singular "pancreatic progenitor" at this stage in vivo.…”
Section: Endodermmentioning
confidence: 99%
“…Is there only one "posterior foregut" route to generate pancreas, or are there multiple such routes, and if so, does the choice of intermediate route impact downstream pancreatic differentiation? Indeed, hPSC differentiation studies have suggested the existence of at least two types of posterior foregut, one poised for pancreatic, and the other primed for liver, differentiation in vitro (Ang et al, 2018). Third, while hPSC differentiation protocols endeavor to generate early Pdx1 + pancreatic progenitors, there is no singular "pancreatic progenitor" at this stage in vivo.…”
Section: Endodermmentioning
confidence: 99%
“…With our interest in characterizing multiple different iPSC-Heps, we tested and found significant differentiation variability and cell death during endoderm induction using popular published protocols (Ang et al, 2018;Ma et al, 2013;Si-Tayeb et al, 2010). In order to better optimize our system, we selected one Matrigel lot for all experiments based on its ability to somewhat support our induction of our weakest iPSC lines; however, even with this Matrigel lot, we did not see efficient differentiation in such lines ( Figure 1C).…”
Section: Induction Of Multiple Ipsc Lines From Different Patients Usimentioning
confidence: 99%
“…Our protocol, for convenience designated ML1 (Figure 1D), showed efficient induction of endoderm. More importantly the ML1 protocol allowed induction of complete monolayers of endoderm from nearly all iPSC lines tested, even those that failed other protocols recommended for poorly differentiating iPSC (Ang et al, 2018;Si-Tayeb et al, 2010).…”
Section: Figure 4)mentioning
confidence: 99%
“…Human pluripotent stem cells (hPSCs), embryonic stem cells (ESCs) [5], and induced pluripotent stem cells (iPSCs) [6] all can differentiate into almost any kind of cell and possess the ability to self-renew indefinitely. Previous researchers have successfully used growth factors and other chemicals to induce differentiation of hPSCs to hPSC-HLCs [7][8][9][10][11], but these studies did not achieve mature hepatic function of hPSC-HLCs in vitro. The results of these studies clearly demonstrate the need to develop new methods to obtain in vitro hepatic function of hPSC-HLCs.…”
Section: Hepatocyte-like Cells Derived From Human Pluripotent Stem Cementioning
confidence: 99%